2014
DOI: 10.1177/096739111402200401
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Property Relationships in Arapaima Gigas Scales Revealed by Nanoindentation Tests

Abstract: Fish scales from Arapaima Gigas have been studied in terms of their structure (morphology, collagen content) and mechanical properties. A strong mechanical gradient was revealed in the scale, hardness and reduced modulus being reduced by a factor of three. Correlations between the hardness and reduced modulus and the mineral content have been found. The external mineral rich layers were determined to be hard and stiff while the inner surface, being collagen rich, was less hard and less stiff. The inside of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…7C). The largest hardness for the arapaima was 1.4 GPa, which is comparable to previous results that range between 1 GPa and 2 GPa [10,33]. Furthermore, the gradient in hardness across the thickness is consistent for the three fish in normalized distance, but very unique when examined in physical distance.…”
Section: Mechanical Behaviorsupporting
confidence: 86%
“…7C). The largest hardness for the arapaima was 1.4 GPa, which is comparable to previous results that range between 1 GPa and 2 GPa [10,33]. Furthermore, the gradient in hardness across the thickness is consistent for the three fish in normalized distance, but very unique when examined in physical distance.…”
Section: Mechanical Behaviorsupporting
confidence: 86%
“…The physical mechanism responsible for the 'pop-in' event may be due to the interaction behavior of the indenter tip with the pre-existing threading dislocation present in the films during mechanical deformation [27]. It was observed that the 'pop-in' depth is corelated with the lattice mismatch of the epitaxial thin film with the substrate, the higher the lattice mismatch the shallower the critical 'pop-in' depth [27,28]. [18,28].…”
Section: Resultsmentioning
confidence: 99%
“…[18,28]. The pop-in event was attributed to the lattice mismatch of the epitaxial films with respect to the substrate [23,27]. Other possible mechanism that would explain the observed behaviour is the formation and propagation of dislocations in GaN thin films [28].…”
Section: Resultsmentioning
confidence: 99%
“…The last component to be formed is an extremely thin layer on top of the surface, which is composed of pure mineral and is referred to as the ''limiting layer.'' [11][12][13] Based on previous studies on the structure and mechanical behavior of elasmoid scales in various fish species, including arapaima, [14][15][16][17][18][19][20][21] red sea bream, 22 bass, 23,24 and tarpon, 11 the protection mechanisms of elasmoid scales have been characterized: the well-mineralized outer layer, including the external layer and limiting layer, provides hardness against the bite from a predator's attack, and the soft collagenous laminated base enables great deformability to dissipate the stored elastic energy through assorted mechanisms, such as lamellar rotation and separation, collagen fibril stretching/compression, fibrillar delamination, and bridging. The synergy of these mechanisms leads to outstanding scale toughness.…”
Section: Progress and Potentialmentioning
confidence: 99%